Sleep, short-term memory, and mood states of volunteers with increasing altitude - Wang, Huanhuan; Li, Xueyan; Li, Jianhua; Gao, Yinghui; Li, Weihua; Zhao, Xinke; Wen, Ruoqing; Han, Jiming; Chen, Kaibing; Liu, Lin (Frontiers in Psychiatry, 2022)
Purpose: This study sought to identify the changes and potential association between sleep characteristics and short-term memory, and mood states among volunteers at different altitudes and times. Method: A total of 26 healthy volunteers were recruited from the PLA General Hospital, and we conducted a longitudinal prospective survey over 1 year from November 2019 to April 2021. First, we collected demographic data, sleep parameters by overnight polysomnography (PSG), short-term memory by digit span test, and mood states by completing a questionnaire with a brief profile of mood states among participants in the plain (53 m). Then, we continuously followed them up to collect data in 3rd month at altitude 1650 m (on 3rd month of 1-year survey period), the 3rd month at altitude 4000 m (on 6th month of 1-year survey period), and the 9th month at altitude 4000 m (on 12th month of 1-year survey period). Results: The prevalence of sleep apnea syndrome (SAS) significantly increased with rising elevation (P＜0.01). Negative mood was more severe and a positive mood increasingly faded with rising elevation (P＜0.001). Additionally, linear correlation analysis showed higher AHI, LAT, and MAT were strongly associated with a greater decline in short-term memory (in 3rd and 9th month at altitude 4000 m, respectively: rs=-0.897, -0.901; rs=-0.691, -0.749; rs=-0.732, -0.794, P＜0.001), also were strongly associated with more severe negative mood . Multiple linear regression pointed that AHI was a significant predictor for negative mood among people at different altitudes. Conclusion: SAS developed easily in high altitudes, most often in CSA (central sleep apnea, CSA). The sleep, short-term memory, and negative mood were significantly more damaged with elevation in volunteers. Sleep parameters were closely associated with short-term memory and mood states in volunteers at high altitude, the higher the sleep parameters (AHI, LAT, MAT) scores, the more significant the mood disorders and the more obvious impairment of short-term memory. AHI was a predictor for the negative mood of volunteers at different altitudes. This study provides evidence that could help with the prevention and control of sleep disorder, cognitive disorder, and negative mood among populations with high altitude.